Production and harvesting of microalgae and an efficient operational approach to biofuel production for a sustainable environment. (1st March 2022) - Khan, Shamshad; Naushad, M.; Iqbal, Jibran; Bathula, Chinna; Sharma, Gaurav
Highlights: Microalgae biofuels are being considered as a long-term option for fossil fuels. Challenges of commercial microalgae production for biofuels are addressed. Recent technical improvements are evaluated in the field of microalgae harvesting. The use of genetic engineering to increase microalgae production is reviewed. Abstract: Biofuel derived from microalgae has developed as an environmentally benign alternative to conventional fossil fuels. Mass production of this biofuel remains difficult due to several of technological and economic issues ranging from commercial production and harvesting of microalgae to biofuel production. The major impediments to establishing an integrated system are large-scale microalgal production and harvesting in a manner that allows for downstream processing to produce biofuels and other useful bioproducts. We integrated and evaluated suspended cultures in open ponds and closed reactors for algal production systems, emphasizing the advantages of attached cultures for algal production. The challenge of harvesting microalgae in liquid growing media has been addressed by technical improvements that have incorporated chemical, mechanical, biological and thermal approaches for dewatering microalgal suspensions and extracting additional bioproducts. Nonbiological approaches such as centrifugation, electrocoagulation, chemical, electrical, and magnetic nanoparticle flocculation, filtering, and biological coculture-based methods were evaluated for their feasibility and considerations in establishing microalgae harvesting systems. The latest breakthroughs in bacteria and fungi-based coculture algae-flocculation technology are discussed. Additionally, this review considers the opportunities for genetic engineering innovation and resources for increasing microalgae production and harvesting, as well as for developing new bioproducts in a sustainable and cost-effective manner.